ChemInform Abstract: A Copper(II) Perchlorate‐Promoted Tandem Reaction of Internal Alkynol and Salicyl N‐Tosylhydrazone: Direct Access to Isochromeno[3, 4‐b]chromene. Issue 1 (January 2015) - Siyang, Hai Xiao; Wu, Xu Rui; Ji, Xiao Yue; Wu, Xin Yan; Liu, Pei Nian
Abstract The presented tandem reaction involves cycloisomerization, formal [4 + 2] cycloaddition and an elimination process.